Time Domains of Hypoxia Responses and -Omics Insights - Yu, James J.; Non, Amy L.; Heinrich, Erica C.; Gu, Wanjun; Alcock, Joe; Moya, Esteban A.; Lawrence, Elijah S.; Tift, Michael S.; O'Brien, Katie A.; Storz, Jay F.; Signore, Anthony V.; Khudyakov, Jane I.; et al. (Frontiers in Physiology, 2022)
The ability to respond rapidly to changes in oxygen tension is critical for many forms of life. Challenges to oxygen homeostasis, specifically in the contexts of evolutionary biology and biomedicine, provide important insights into mechanisms of hypoxia adaptation and tolerance. Here we synthesize findings across varying time domains of hypoxia in terms of oxygen delivery, ranging from early animal to modern human evolution and examine the potential impacts of environmental and clinical challenges through emerging multi-omics approaches. We discuss how diverse animal species have adapted to hypoxic environments, how humans vary in their responses to hypoxia (i.e., in the context of high-altitude exposure, cardiopulmonary disease, and sleep apnea), and how findings from each of these fields inform the other and lead to promising new directions in basic and clinical hypoxia research.